A147 RESPONSE AND REMISSION AFTER 16 WEEKS OF USTEKINUMAB– AN ALL PATIENTS ANALYSIS FROM THE UNITI CROHN'S STUDIES. (1st March 2018) - Colombel, J F; Sloan, S; Gasink, C; Gao, L; Jacobstein, D; Lee, S D; Targan, S
Abstract: Background: Ustekinumab(UST) has been shown to induce & maintain clinical response & remission in moderate-severe Crohn's disease(CD) in 2 induction[(UNITI-1(anti-TNF failures) & UNITI-2(anti-TNF non-failures) & 1 maintenance(IM-UNITI)] randomized, PBO-controlled Ph3 trials. Aims: We evaluated efficacy (response & remission) for all pts who received an IV induction dose of approximately 6mg/kg, including responders(CDAI decrease ≥100) & non-responders, 8wks after first UST maintenance dose of 90mg SC, i.e. 16wks from the IV induction dose. Methods: Pts achieving clinical response 8wks after a single IV induction dose were randomized to SC PBO, UST 90mg q12wks or q8wks. UST pts not in clinical response 8wks after IV induction dose were given UST90mg SC & if in clinical response 8wks later were continued on 90mg SC q8w dosing. A total of 458pts were exposed to an IV induction dose of 6mg/kg(UNITI-1, N=249 & in UNITI-2 N=209) with a response rate at wk8 of 37.8% & 57.9% vs. PBO response rate of 20.2% & 32.1% respectively. The remission rate at wk8 in UNITI-1 & UNITI-2 was 20.9% & 40.7 vs. PBO of 7.3% & 19.6% respectively. For this evaluation, response & remission status of the entire population exposed to an IV induction dose of 6mg/kg of UST was evaluated 8wks after the first SC maintenance dose of UST. All pts who received 6mg/kg IV UST induction were included, including responders randomized to SC PBO (who did not receive SC UST at wk8). Results: Of the 219 pts not in clinical response to a single UST IV induction dose in UNITI 1&2, 37.6% & 60.5% respectively were in clinical response 8wks after the first maintenance UST dose (90 mg SC). Evaluating all pts exposed to 6mg/kg IV UST induction, response rates 8wks after the first SC injection (16wks after the IV induction dose) for UNITI1&2 were 47.4% & 73.7% respectively. In the sub-population who were anti-TNF naïve upon enrolment into UNITI-2 (n=144), at 8 weeks after the first SC injection, 72.9% were in clinical response and 60.4% were in clinical remission. Conclusions: These numbers at wk16 are expected to reflect real world experience in pts who receive the induction dose & one additional maintenance dose 8wks later. The resulting rates of response & remission are higher than previously reported in induction studies across all populations (anti-TNF non-failures & anti-TNF failures). About 73% of anti-TNF non-failures attain clinical response & over half are in remission. The data support the clinical rationale for providing at least one SC maintenance dose of UST irrespective of clinical response 8wks after IV induction to assess UST benefit. Funding Agencies: Janssen Research & Development, LLC funded this study